2018
DOI: 10.1002/icd.2079
|View full text |Cite
|
Sign up to set email alerts
|

I hear your yes‐no questions: Children's response tendencies to a humanoid robot

Abstract: This study investigated the responses of 4‐ and 5‐year‐old Japanese children to yes‐no questions about familiar and unfamiliar objects that were asked by a communicative or a non‐communicative humanoid robot. The children in the communicative condition watched a pretrial video in which a humanoid robot interacted with a human adult, and those in the non‐communicative condition watched a pretrial video in which the same humanoid robot was unresponsive to the same human adult's utterances and actions. Then, all … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
20
0
2

Year Published

2019
2019
2021
2021

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 11 publications
(22 citation statements)
references
References 22 publications
0
20
0
2
Order By: Relevance
“…A recent review of the literature by Marchetti et al (2018) showed that different physical characteristics of HSRs may significantly affect the quality of interaction between humans and robots at different ages. The construction of robots that integrate and expand the specific biological abilities of our species led to two different directions in robotic development based on different, though related, theoretical perspectives: developmental cybernetics (DC; Itakura, 2008 ; Itakura et al, 2008 ; Moriguchi et al, 2011 ; Kannegiesser et al, 2015 ; Okanda et al, 2018 ; Di Dio et al, 2019 ; Wang et al, 2020 ; Manzi et al, 2020a ) and developmental robotics (DR; De La Cruz et al, 2014 ; Cangelosi and Schlesinger, 2015 , 2018 ; Lyon et al, 2016 ; Morse and Cangelosi, 2017 ; Vinanzi et al, 2019 ; Zhong et al, 2019 ; Di Dio et al, 2020a , b ). The first perspective (DC) consists of creating a human-like system, by simulating human psychological processes and prosthetic functions in the robot (enhancing the function and lifestyle of persons) to observe people’s behavioral response toward the robot.…”
Section: Introductionmentioning
confidence: 99%
“…A recent review of the literature by Marchetti et al (2018) showed that different physical characteristics of HSRs may significantly affect the quality of interaction between humans and robots at different ages. The construction of robots that integrate and expand the specific biological abilities of our species led to two different directions in robotic development based on different, though related, theoretical perspectives: developmental cybernetics (DC; Itakura, 2008 ; Itakura et al, 2008 ; Moriguchi et al, 2011 ; Kannegiesser et al, 2015 ; Okanda et al, 2018 ; Di Dio et al, 2019 ; Wang et al, 2020 ; Manzi et al, 2020a ) and developmental robotics (DR; De La Cruz et al, 2014 ; Cangelosi and Schlesinger, 2015 , 2018 ; Lyon et al, 2016 ; Morse and Cangelosi, 2017 ; Vinanzi et al, 2019 ; Zhong et al, 2019 ; Di Dio et al, 2020a , b ). The first perspective (DC) consists of creating a human-like system, by simulating human psychological processes and prosthetic functions in the robot (enhancing the function and lifestyle of persons) to observe people’s behavioral response toward the robot.…”
Section: Introductionmentioning
confidence: 99%
“…Even though this tendency was much weaker than in 2and 3-year-olds, Okanda and colleagues proposed that older Japanese preschoolers have a mild tendency to say "yes" when they feel social pressure from unfamiliar adults. In fact, older children did not show a similar attitude to familiar adults such as mothers (Okanda et al, 2012) or unfamiliar adults and robots in videos (Okanda et al, 2013;Okanda, Zhou, Kanda, Ishiguro, & Itakura, 2018).…”
mentioning
confidence: 89%
“…[139] . 研究也发现, 孩子喜欢那些展现出社会能力和 温暖的拟人化社会机器人 [15] . 在教育机器人的设计上, 大学生更偏好具有人类特征和最小面部特征的机器人, 同时还要求机器人能够体现出基本情绪(尤其是积极 情绪)以及尽责、随和、开放等积极人类品质 [140] .…”
Section: 拟人化是机器人接受度的核心unclassified
“…[13] . 机器人外观的重要性 在不同的被试群体中都得到了验证, 如社会机器人通 常面向的老人群体 [14] 和儿童群体 [15] . 此外, 对机器人 外观的研究也涵盖了许多不同的维度, 如机器人的高 度 [16] 、重量 [14] 、性别特征 [17] 和拟人化程度 [18] 等.…”
unclassified